Formação de professores de História em cursos de Licenciatura a distância: um estudo nas IES Uniube e Unimontes - Cunha, Valeska Guimarães Rezende da (2014)
The central object of this research is about History teachers‟ background, in Distance Education, in particular, in the institutions - Montes Claros State University (UNIMONTES) and Uberaba University (UNIUBE), institutions providers of this type of education. The general objective was to analyze the political-pedagogical projects, the curriculum, the knowledge and the pedagogical practices in initial training courses for History teachers, in the modality of Distance Education, focusing on weaken and improvers aspects. The methodology adopted is situated in the qualitative approach of educational research, having been carried out a multiple case study. The procedures and the sources used were: the bibliographic research, content analysis of official documents; and the application of a questionnaire to teachers of these investigation. The initial sample was composed of 73 employees: managers, teachers trainers and tutors of these institutions, and the data obtained correspond to 33 participants. For recording and analysis of the data we use the digital search tools: a tool was \"Google docs\", which allowed for the submission of the questionnaire to the subjects involved in the research, via the Internet; the other tool was the Tropes software, version 8.4.2 of February 2014, which helped in the analysis of the data obtained through the questionnaire. The results showed several weaknesses in the cases studied: the ignorance of the PPP by many teachers; the instability of the teachers in the courses; the fragmentation of content; the conditions of telecommunications; the lack of integration of multidisciplinary team; evaluation processes without rigor; the prejudice against this modality; the difficult access to virtual platforms; the absence of research in courses; according to the teacher, the students don´t go beyond the textbook available; no training of tutors to follow-up the students; the lack of qualification of the students and the fears in relation to the use of technologies; the lack of learning to read, interpret, and solve problems individually or collectively; the not search for autonomy; difficulties in learning to learn and lack of technology; the behavior of the students in relation to the daily working hours of study. Among the potential, we highlight: the commitment of teachers; the indication of complementary and obligated readings in didactic material; the trust as part of the multidisciplinary team to develop the educational materials; the belief in the modality for the continued education; the opportunity for initial training, whereas the distancing of the students in relation to training centers; the pedagogical potential of Distance Education; the involvement of teachers with pedagogical practice; the courses made by teachers to act in the this modality; and the belief in the use of technology as an important element in the process of teaching and learning. We believe that these indicators may provoke discussions and contribute to the improvement of the quality of education, in particular the History teachers‟ background, in Distance Education.